Association between dietary intake, body measurements, and urinary bone resorption markers in young adults with osteopenia and osteoporosis: a cross-sectional study - Mi-Hyun Kim; Mi-Kyeong Choi (Korean Journal of Community Nutrition, 2023)
Objectives: Bone health in early adulthood, as individuals approach peak bone mass, plays a critical role in preventing osteoporosis later in life. This study aimed to investigate the associations between lifestyle and dietary factors, anthropometric measurements, and urinary bone resorption markers in young adults.